Excitation functions and isomeric cross section ratio of the Ni58(n,p)58Com,g reactions from 2 to 15 MeV - Cs M. Buczkó (2018)
The cross sections for the Ni58(n,p)58Com,g reactions were measured in the neutron energy range 2.1-14.8 MeV using the activation technique in combination with high-resolution gamma-ray spectroscopy. Neutrons were produced via the H2(d,n)3He and H3(d,n)4He reactions using solid TiD, TiT, and deuterium gas targets. The isomeric cross section ratio was determined in the 5.38-12.2 MeV range and at 14.8 MeV neutron energy. Statistical model calculations taking into account precompound effects were performed for the formation of the isomeric and ground states of the Co58. The calculational results based on the ''back-shifted'' level density model agree well with the measured excitation functions and render possible the selection of the most probable values of isomeric cross section ratios among the discrepant data obtained around 2 and 14 MeV neutron energies. © 1995 The American Physical Society.